Heresy, confession and inquisition in medieval ecclesiastical government. The political dimension of the pastoral judgment - Belle Irene (Global Writing Academica Researching & Publishing, 2019)
The article aims to highlight the political dimension –in a broad sense– of confession and the inquisition in their emergence as procedures to sentence hidden sin. It does so by inserting both in the dual forms, pastoral and juridical, that the plenomedieval ecclesiastical government develops for the condemnation of the disobedience to the new Roman orthodoxy and orthopraxis. In this respect, the confe-sional and inquisitorial devices are understood in relation to the emergence of the heretical as a stubborn challenge to the Roman government - in the tension between the government of oneself and of othersThe article aims to highlight the political dimension –in a broad sense– of confession and the inquisition in their emergence as procedures to sentence hidden sin. It does so by inserting both in the dual forms, pastoral and juridical, that the plenomedieval ecclesiastical government develops for the condemnation of the disobedience to the new Roman orthodoxy and orthopraxis. In this respect, the confe-sional and inquisitorial devices are understood in relation to the emergence of the heretical as a stubborn challenge to the Roman government - in the tension between the government of oneself and of others